Inhalational exposure to particulate matter air pollution alters the composition of the gut microbiome. (September 2018) - Mutlu, Ece A.; Comba, Işın Y.; Cho, Takugo; Engen, Phillip A.; Yazıcı, Cemal; Soberanes, Saul; Hamanaka, Robert B.; Niğdelioğlu, Recep; Meliton, Angelo Y.; Ghio, Andrew J.; Budinger, G.R. Scott; Mutlu, Gökhan M.
Abstract: Recent studies suggest an association between particulate matter (PM) air pollution and gastrointestinal (GI) disease. In addition to direct deposition, PM can be indirectly deposited in oropharynx via mucociliary clearance and upon swallowing of saliva and mucus. Within the GI tract, PM may alter the GI epithelium and gut microbiome. Our goal was to determine the effect of PM on gut microbiota in a murine model of PM exposure via inhalation. C57BL/6 mice were exposed via inhalation to either concentrated ambient particles or filtered air for 8-h per day, 5-days a week, for a total of 3-weeks. At exposure's end, GI tract tissues and feces were harvested, and gut microbiota was analyzed. Alpha-diversity was modestly altered with increased richness in PM-exposed mice compared to air-exposed mice in some parts of the GI tract. Most importantly, PM-induced alterations in the microbiota were very apparent in beta-diversity comparisons throughout the GI tract and appeared to increase from the proximal to distal parts. Changes in some genera suggest that distinct bacteria may have the capacity to bloom with PM exposure. Exposure to PM alters the microbiota throughout the GI tract which maybe a potential mechanism that explains PM induced inflammation in the GI tract. Graphical abstract: Image 1 Highlights: Examine gut microbial composition after inhalational exposure to particulate matter (PM) mimicking real life human exposures. Gut microbiome at five sampling sites (stomach, small intestine, cecum, colon, feces) were examined concurrently. PM-induced gut microbial changes which may affect inflammatory diseases of the gastrointestinal tract. Abstract : Exposure to particulate matter air pollution alters the gut's microbial composition, which could be a potential mechanism that supports particulate matter induced inflammation in the gastrointestinal tract.